Aeration efficiency of free-surface conduit flow systems - Unsal, M.; Baylar, A.; Tugal, M.; Ozkan, F. (Taylor & Francis Ltd, 2009)
Dissolved oxygen is a measure of the quantity of oxygen present in water and is one of the best indicators of the health of a water ecosystem. Dissolved oxygen levels in water can be increased by creating turbulent conditions where fine air bubbles are carried into the bulk of the flow. This is achieved by hydraulic structures. A free-surface conduit is a particular instance of this. In the present work, a series of experiments were conducted to investigate the aeration efficiency of free-surface conduit flow systems. The results indicate that free-surface conduit flow systems are very effective for oxygen transfer. At Froude numbers greater than 15, almost full oxygen transfer up to the saturation value was reached. Moreover, from experimental data, a regression equation was obtained with a very high correlation coefficient, showing the effect of various parameters on the aeration efficiency.
Keywords: aeration efficiency; air entrainment; conduit; dissolved oxygen; oxygen transfer